Bank Ownership and Financial Stability - Enrico Perotti; Marcel Vorage (Tinbergen Institute, 2010)
We study a politician's choice for state or private control of banks. The choice trades of lobbying contributions against social welfare, weighted by political accountability.Politicians facing few constraints prefer state control to maximize their rents. As state banks are less efficient, at higher level of accountability there is a shift to private control. At the transition point there is a jumpin risk taking, as private banks do not internalize the social costs of bank failure. To discourage private risk taking, the politician leaves more rentsto private banks.We conclude with some suggestive data complementing existing evidence that financial instability is highest when bank control is capturedby small lobbies.
Keywords: D70; G21; G28; 330; Political Economy; Bank Control; Lobbying; Instability; Bankenaufsicht; Privatisierung; Interessenpolitik; Bankenkrise; Wirkungsanalyse; Neue politische Ökonomie